2018
DOI: 10.1111/2041-210x.12993
|View full text |Cite
|
Sign up to set email alerts
|

Field testing a novel high residence positioning system for monitoring the fine‐scale movements of aquatic organisms

Abstract: Acoustic telemetry is an important tool for studying the behaviour of aquatic organisms in the wild.VEMCO high residence (HR) tags and receivers are a recent introduction in the field of acoustic telemetry and can be paired with existing algorithms (e.g. VEMCO positioning system [VPS]) to obtain high‐resolution two‐dimensional positioning data.Here, we present results of the first documented field test of a VPS composed of HR receivers (hereafter, HR‐VPS). We performed a series of stationary and moving trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 24 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…The accuracy in the present study was better than, or equivalent to, that reported in comparable studies using commercial positioning systems. For example, Espinoza, Farrugia, Webber, et al () showed that the mean positional accuracy of VEMCO Positioning System (VPS) estimates from a stationary transmitter deployed at several locations within the receiver array was 2.64 ± 2.32 m. In comparison, Guzzo et al () found that the accuracy estimates of HR‐VPS positions for all stationary trials was 5.6 m. Biesinger et al () demonstrated a positional accuracy of approximately 2 m. This improved accuracy could be explained by (a) the positioning of the receiver to the nearest centimetre using a theodolite for x and y coordinates, and using a decametre for z , and (b) the real‐time measurement of water temperature to continuously correct the speed of sound in water at the exact moment of acoustic signal reception. This was possible using the intern thermic sensor included in Thelma Biotel receivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy in the present study was better than, or equivalent to, that reported in comparable studies using commercial positioning systems. For example, Espinoza, Farrugia, Webber, et al () showed that the mean positional accuracy of VEMCO Positioning System (VPS) estimates from a stationary transmitter deployed at several locations within the receiver array was 2.64 ± 2.32 m. In comparison, Guzzo et al () found that the accuracy estimates of HR‐VPS positions for all stationary trials was 5.6 m. Biesinger et al () demonstrated a positional accuracy of approximately 2 m. This improved accuracy could be explained by (a) the positioning of the receiver to the nearest centimetre using a theodolite for x and y coordinates, and using a decametre for z , and (b) the real‐time measurement of water temperature to continuously correct the speed of sound in water at the exact moment of acoustic signal reception. This was possible using the intern thermic sensor included in Thelma Biotel receivers.…”
Section: Discussionmentioning
confidence: 99%
“…To position tagged aquatic animals accurately without links to receivers, analysis of Time Difference Of Arrival (TDOA) has been developed by telemetry manufacturers. Unfortunately, scientific studies using this methodology have not provided sufficient details of the technical methods and calculations to enable reported experiments to be reproduced (see for instance Espinoza, Farrugia, Webber, Smith, & Lowe, ; Guzzo et al, ; Roy et al, ). Moreover, until recently, access to this methodology was via a paid service or software, not via open access services (Baktoft, Gjelland, Økland, & Thygesen, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of synthetic aperture position estimates is dependent first on the precision of the timing and on geometry of the aperture based on theory of minimizing the intersect area of possible reception spheres or circles (termed dilution of precision, Schau and Robinson ; Pascazio and Fornaro ). Geometry is confirmed in practice as the most consistent determinant of quality in estimates from moored array hydrophone positioning systems (Meckley et al ; Romain et al ; Steel et al ; Guzzo et al ) and for those made by a towed hydrophone (Nielsen et al ).…”
mentioning
confidence: 91%
“…A frequently used signal encoding is pulse position modulation (PPM), where the ID is encoded in the time interval between 8 to 10 transmitted pulses, similar to Morse code [9,10]. Since a PPM transmission takes 3 to 5 seconds [11], simultaneous transmissions of different animals can cause signal collision, which results in incomplete or corrupted transmissions. Hence, the amount of fish that will be present simultaneously in the study area limits the allowable burst interval.…”
Section: Introductionmentioning
confidence: 99%